2016
DOI: 10.1080/09546634.2016.1218417
|View full text |Cite
|
Sign up to set email alerts
|

A new topical panthenol-containing emollient: skin-moisturizing effect following single and prolonged usage in healthy adults, and tolerability in healthy infants

Abstract: Purpose: Two studies were conducted with a new topical panthenol-containing emollient (NTP-CE) to investigate the skin-moisturizing effect in healthy adults and tolerability in healthy infants. Methods: In Study 1 (N ¼ 44), a single skin application of NTP-CE was performed followed by a 4-week twice-daily application. Skin hydration and stratum corneum (SC) water content change (using Raman spectroscopy) were measured. In the 4-week Study 2 (N ¼ 65, aged 3-25 months), NTP-CE tolerability was assessed using a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
(47 reference statements)
3
25
0
1
Order By: Relevance
“…In another set of two studies, Stettler et al (34) investigated the skin moisturizing effect of the dexpanthenol-containing emollient in healthy adults with dry skin and in healthy infants. Study 1 (N ¼ 44) was a randomized, intra-individual comparison study while study 2 was a non-comparative trial (N ¼ 65, age: 3-25 months).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…In another set of two studies, Stettler et al (34) investigated the skin moisturizing effect of the dexpanthenol-containing emollient in healthy adults with dry skin and in healthy infants. Study 1 (N ¼ 44) was a randomized, intra-individual comparison study while study 2 was a non-comparative trial (N ¼ 65, age: 3-25 months).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…The use of RS to examine lateral packing and conformational order of SC lipids is well established, as well as in evaluations of SC water profiles [198], and determinations of lipid/protein ratio through calculations of lipid and protein intensity peaks [199]. Such attributes have been employed in a variety of skin-related studies of barrier permeability in dry skin conditions [199][200][201][202], substance penetration [203], and evaluations of the efficacy of moisturisers [204] and anti-ageing ingredients and formulations [56,205].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Results from Raman spectroscopy implied a NTP-CE-mediated relocation of the water molecules from upper to deeper layers of the stratum corneum leading to deep moisturization. NTP-CE also exerted favorable effects on the skin microflora (13,14). Moreover, in a study in healthy infants (aged 3-25 months) twice-daily application of NTP-CE for 4 weeks was well-tolerated and significantly increased skin hydration (14).…”
Section: Introductionmentioning
confidence: 95%
“…A new topical panthenol-containing emollient (NTP-CE, Bepanthen V R SensiDaily) (Bayer Consumer Care AG, Basel, Switzerland) has been developed for subjects with non-inflammatory dry and sensitive skin conditions, such as AD while in remission phase (13,14). Previous studies with NTP-CE in healthy adult subjects showed that its application is associated with significant improvements in skin barrier restoration, skin moisturization, and intercellular lipid layer organization in the stratum corneum.…”
Section: Introductionmentioning
confidence: 99%